2018
DOI: 10.1038/s41431-018-0106-6
|View full text |Cite
|
Sign up to set email alerts
|

Views of rare disease participants in a UK whole-genome sequencing study towards secondary findings: a qualitative study

Abstract: With large-scale genome sequencing initiatives underway, vast amounts of genomic data are being generated. Results—including secondary findings (SF)—are being returned, although policies around generation and management remain inconsistent. In order to inform relevant policy, it is essential that the views of stakeholders be considered—including participants who have made decisions about SF since the wider debate began. We conducted semi-structured interviews with sixteen rare disease patients and parents enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 29 publications
6
45
0
Order By: Relevance
“…This included misunderstandings about what types of conditions were included on the list of secondary findings (participants were informed they would learn about clinically 'actionable' findings, which was the term used in the consent form, however, we have observed that consenters did frequently cite 'cancer' and 'heart disease' during consent appointments [28]), as well as whether they had personally opted to receive to secondary findings. These findings are consistent with a previous UK study in which many participants couldn't recall their decision about secondary findings at the time of consent [15]. Where our findings add to the existing research is that we also found that several parents felt it was overwhelming to have the conversation about secondary findings at the same time as the conversation about the main findings.…”
Section: Issues Around Secondary Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…This included misunderstandings about what types of conditions were included on the list of secondary findings (participants were informed they would learn about clinically 'actionable' findings, which was the term used in the consent form, however, we have observed that consenters did frequently cite 'cancer' and 'heart disease' during consent appointments [28]), as well as whether they had personally opted to receive to secondary findings. These findings are consistent with a previous UK study in which many participants couldn't recall their decision about secondary findings at the time of consent [15]. Where our findings add to the existing research is that we also found that several parents felt it was overwhelming to have the conversation about secondary findings at the same time as the conversation about the main findings.…”
Section: Issues Around Secondary Findingssupporting
confidence: 91%
“…However, participants' main concern about secondary findings was the potential psychological harm that the results might have on them. This concern has been identified in previous qualitative research [12,15]. In our previous observational study [28], most of the consent conversation was dedicated to providing patients with biomedical information and information about the project, e.g.…”
Section: Issues Around Secondary Findingsmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar qualitative studies have explored parents’ attitudes toward childhood genetic testing for cancer (Alderfer et al, ; Bradbury et al, ; Godino, Jackson, Turchetti, Hennessy, & Skirton, ), autism spectrum disorders (Chen et al, ; Chen, Xu, Huang, & Dhar, ), and deafness (Mackley et al, ) in Western countries. This is a qualitative investigation that has explored parents’ in‐depth opinions toward genetic testing for IRDs in a Chinese population.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings revealed that parents with low educational levels and annual household incomes tended to have relatively low levels of knowledge and awareness of genetic testing. Most published studies on genetic testing for children had focused on highly educated parents in high‐income countries (Alderfer et al, ; Chen et al, ; Lim et al, ; Mackley et al, ), and we approached this important topic in a very different environment.…”
Section: Discussionmentioning
confidence: 99%